Pengaruh Penambahan Spirulina Terhadap Sifat Fisikokimia, Sensoris, dan Aktivitas Antioksidan Snack Bar - Artika, I Made Mahardika Reynata Putra; Suparthana, Putu; Rai Widarta, I Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2025)
Snack bars is a convenient and practical food that can quickly provide a source of energy and nutrients. Snack bars are typically made from a mixture of cereals, nuts, seeds, dried fruits, and sweeteners like honey or syrup. Snack bars can be made using local ingredients, but most locally made snack bars still contain allergens. Corn has the potential to be used as a substitute ingredient but still has unbalanced nutritional content. Therefore, spirulina can be used to balance the nutrients in snack bars, as spirulina is a microscopic algae rich in protein, vitamins, minerals, and bioactive compounds. The addition of spirulina aims to enhance the nutritional value and turn it into functional food. This study uses a completely randomized design (CRD) with five levels of spirulina addition: 0%, 2%, 3%, 4%, and 5%. Each level is repeated three times, resulting in 15 experimental units. The parameters observed include protein content, fat content, antioxidant activity, texture profile, color profile, and sensory acceptance. The data obtained were then analyzed using analysis of variance (ANOVA), and if significant effects were found, Duncan's Multiple Range Test was conducted. The results showed that the addition of spirulina significantly increased the protein content, antioxidant activity, texture, and color of the snack bar. However, no significant effect was found on the fat content and sensory characteristics of the snack bar. The addition of 5% spirulina produced the best snack bar characteristics with a protein content of 8.53%, fat content of 6.63%, antioxidant activity of 63.67%, a texture profile of 54.04 N, and a color profile with L* value of 16.38, a* value of -1.60, and b* value of -8.17. The hedonic test, which includes color, aroma, texture, taste, and overall acceptance, was rated as “slightly liked” . Keyword s : spirulina, snack bar, functional food